ANALISIS PENGARUH VARIASI TEKANAN GAS DAN PERSENTASE KETEBALAN LAPISAN BOUNDING DAN COATING PADA PROSES REBUILD-UP MATERIAL BAJA AISI 1045 DENGAN METODE ARC SPRAY TERHADAP TINGKAT KEREKATAN ANTAR LAPISAN - Fathani Adhitya Mamang; Bachtiar Bachtiar; Imam Khoirul Rohmat; Adri Fato (P3M Politeknik Negeri Indramayu, 2023)
Each engine component has the durability that can decrease and wear due to continuous friction. The thermal spray method is an alternative that is used. The type of thermal spray that is found in the industry is Arc Spray. However, the peeling of the coating metal with the substrate is one of the problems. In this study, the variables that have contributed to the peeling of the coating layer were taken. The variables compared are the total thickness of the bounding and coating layers of 1 mm with a percentage of 50% : 50% and 30% : 70%. Another variation is gas pressure of 2 Bar, 3 Bar and 4 Bar in rebuild-up process of AISI 1045. Specimens with thickness percentage of 30% : 70% have significant difference in tensile strength value compared to the thickness percentage of 50% : 50% with an average difference of 5.02 MPa; 4.8975 MPa and 3.29 MPa in specimens with a gas pressure of 2 bar; 3 bars; 4 bars. The influences of thickness of bound and top coat have percentage effect 21.12% on each layer. As the gas pressure increases, the bonding value is higher because the higher gas, the smaller porosity which is proved by microstructural tests.